2019
DOI: 10.1111/ejss.12767
|View full text |Cite
|
Sign up to set email alerts
|

Organic and inorganic amendments did not affect microbial community composition in the bulk soil differently but did change the relative abundance of selected taxa

Abstract: Deep placement of organic amendments such as poultry litter and legume residues has been developed as a technique to ameliorate sodic clay subsoils in the south‐east Australian cropping region. It has been suggested that the soil microbial community plays a key role in this process of subsoil amelioration. A controlled environment experiment using repacked soil units was conducted to investigate changes in the microbial communities of subsoil treated with organic and inorganic amendments. Poultry litter, inorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The reason may be that SOSC had the advantages of organic and inorganic fertilizers simultaneously. Plants can use the inorganic nutrients in liquid form instantly 41 . Nitrogen, however, is not able to be immediately available for plant uptake until mineralization in organic cropping system, although organic fertilizers can increase soil particle and soil aggregates and improve N fixation ability of soils 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason may be that SOSC had the advantages of organic and inorganic fertilizers simultaneously. Plants can use the inorganic nutrients in liquid form instantly 41 . Nitrogen, however, is not able to be immediately available for plant uptake until mineralization in organic cropping system, although organic fertilizers can increase soil particle and soil aggregates and improve N fixation ability of soils 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Plants can use the inorganic nutrients in liquid form instantly. 41 Nitrogen, however, is not able to be immediately available for plant uptake until mineralization in organic cropping system, although organic fertilizers can increase soil particle and soil aggregates and improve N fixation ability of soils. 42 This phenomenon indicated that it had a positive impact on reducing soil nutrient losses and increasing plant nutrients utilization to substitute the mineral fertilizers partially or completely with organic fertilizers.…”
Section: Effects Of Combination Of Organic and Chemical Fertilizers Omentioning
confidence: 99%
“…Studies have determined that the use of DBAs facilitate increases in bacterial abundance as well as changes in community‐level composition (Celestina, Sale, Hunt, et al, 2019; Celestina, Sale, Tang, & Franks, 2019; Celestina, Wood, Manson, et al, 2019; Wang et al, 2020). However, when the plant growth response is considered, soil bacteria likely respond to DBAs via direct and indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The direct response is primarily governed by bacteria responding to DBA increased nutrient availability, altered C and N source availability and decreased soil pH (Leff et al, 2015; Wang et al, 2020). However, as the amendment source is deep banded, and not mixed within the subsoil, a significant distance‐dependent effect is likely, with a greater bacterial response expected within the DBAs detritusphere compared to the bulk soil (Celestina, Sale, Tang, & Franks, 2019; Kuzyakov & Blagodatskaya, 2015). This is hypothesised to be driven by higher nutrient concentration and more pronounced soil physicochemical modifications immediately surrounding the DBAs.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al () used a pulse‐labelling approach to reveal that N fertilization increased belowground C in paddy rice systems that was confined to the root biomass and rhizosphere, particularly in the early growth stages. The paper by Celestina, Sale, Tang, and Franks () reports how organic and inorganic amendments, applied principally to ameliorate sodic soils, can affect the microbial community in the surrounding bulk soil, suggesting the migration of nutrients away from their source. Lee, Hwang, Park, Kim, and Lee () report that the use of film mulching, used to increase crop yields by improving soil moisture and temperature condition, increased the respiration of C and hence potential loss of SOM.…”
mentioning
confidence: 99%